Galerie Hauser & Wirth : Catalogue - I - 1996. - Wirth, Iwan (Zürich : Galerie Hauser & Wirth, 1996)
Arp, Hans (Jean) ; Baselitz, Georg ; Beuys, Joseph ; Bill, Max ; Ernst, Max ; Gris, Juan ; Klee, Paul ; Martin, Agnes ; Paik, Nam June ; Picabia, Francis ; Polke, Sigmar ; Richter, Gerhard ; Rothko, Mark
Duits
boek